Theoretical aspects of magnetic, magnetocaloric, and critical exponents: Nanomaterial model. (15th January 2023) - Arejdal, M.
Graphical abstract: Highlights: The nano-material is analyzed. Magnetization is determined. The magnetocaloric effect of the nanomaterial formed on Dendrimer structure is studied. Isothermal magnetic entropy change, relative cooling power (RCP) and the capacity of refrigeration for the different external magnetic field are established. The critical exponents β, γ and δ are calculated. Abstract: In this present research paper, our focus was on studying the nanomaterial model with the spin vector and its amplitude was 5/2: the magnetic, magnetocaloric effect and the critical exponents. By using Monte Carlo method, I succeeded in determining the fact that the magnetic transition nature was second-order with the Curie temperature of TC = 14.46 K. The maximum magnetic entropy change (of) (ΔSM ) of 3.53 J kg -1 K −1, the large Relative Cooling Power (RCP) of 32.67 J kg −1 and the corresponding maximum Refrigeration Capacity (RC) of 24.50 J kg −1 were established under the magnetic field of 8 T. The critical exponents were determined with the purpose of studying the nature and underlying mechanism of the Ferromagnetic (FM) to the Paramagnetic (PM) phase transition. The critical exponents were obtained using magnetocaloric data from the field dependence of the magnetic entropy, the relative cooling power and Widom scaling relation. β, γ and δ indicated that the nanomaterial model belonged to the two-dimensional (2D)-Ising model with long-range interaction.